(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article discusses and analyzes the use of learning technology in collaboration in Russian language lessons. The main idea of this technology is to create conditions for active joint learning activities of students in different learning situations. The bottom line is that the student wants to acquire knowledge himself. Collaboration just gives an excellent incentive for cognitive activity, for communication, since in this case you can always count on help from comrades.